GEOGRAPHICAL LABOUR MOBILITY IN SPAIN - A PANEL DATA APPROACH - Ana Angulo; Jesus Mur (European Regional Science Association (ERSA), 2005)
In this paper, we study geographical labour mobility taken by workers in Spain from a regional standpoint. Using a panel data set referred to the evolution of these decisions in the 1990-2003 period, the main objective is to determine what are the main variables that influence in labour mobility as well as to quantify their impact. To this respect, regional labour market status, spatial variations in employment opportunities and house prices have turned to be the main determinants. Furthermore, also certain socio-demographic characteristic of workers such as education, marital status and the presence of children in the household are also of great relevant.
Keywords: 330